2021
DOI: 10.1007/s40261-021-01011-y
|View full text |Cite
|
Sign up to set email alerts
|

Overall Efficacy and Safety of Safinamide in Parkinson’s Disease: A Systematic Review and a Meta-analysis

Abstract: Background and Objective Safinamide is a novel anti-parkinsonian drug with possible anti-dyskinetic properties. Parkinson's disease (PD) is a complex disease. The objective of this systematic review and meta-analysis is to evaluate the efficacy and safety of safinamide administration compared to placebo in PD patients on multiple outcomes. Methods PubMed, EMBASE, Cochrane CENTRAL, LILACS, and trial databases were searched up to 23 December 2020 for randomized controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…Compared to the score at V1, the change in the score at V2 and V3 for the BDI-II, NMSS mood/ apathy domain, and the PDQ-39 emotional well-being domain was significant too, but differences were not observed between the score from V2 and V3 to V4 for any of the scales (Table 2 and Figs. 1,2,3). With regard to the MDS-IV and Judd criteria, at the baseline visit, 2% (N = 1) of patients presented nonD, 12% (N = 6) subD, 34% (N = 17) mD, and 52% (N = 26) suffered MD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the score at V1, the change in the score at V2 and V3 for the BDI-II, NMSS mood/ apathy domain, and the PDQ-39 emotional well-being domain was significant too, but differences were not observed between the score from V2 and V3 to V4 for any of the scales (Table 2 and Figs. 1,2,3). With regard to the MDS-IV and Judd criteria, at the baseline visit, 2% (N = 1) of patients presented nonD, 12% (N = 6) subD, 34% (N = 17) mD, and 52% (N = 26) suffered MD.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of changes in mood was a secondary objective defined in the study protocol. Patients were enrolled according to the following inclusion criteria: (1) diagnosis of PD according to the UK Parkinson's Disease Society Brain Bank criteria [8]; (2) to have the indication of receiving safinamide according to the neurologist criteria in their clinical practice; (3) to have a Non-Motor Symptoms Scale (NMSS) total score at baseline of at least 40; (4) no dementia criteria with a Mini-Mental State Examination at baseline of at least 26) [9]; (5) to be older than 30 years old; (6) to wish to voluntarily participate and to sign a consent form. Exclusion criteria were (1) to be under MAOB-I (rasagiline or selegiline; a washout period of at least 2 week was allowed); (2) any other contraindication to be treated with safinamide according to product data; (3) incapacity to complete the questionnaires adequately; (4) other disabling concomitant neurological disease (stroke, severe head trauma, neurodegenerative disease, etc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Safinamide is marketed in Europe and in North America under the brand name of Xadago® (Zambon Pharma) and Onstryv® (Valeo Pharma); it was approved in 2015 as adjunctive therapy to levodopa in mid- to late-stage fluctuating patients and became commercially available in the spring of 2016. While its efficacy in controlling motor symptoms and improving motor fluctuations is well established 9 11 , uncertainty remains on its potential ability to control dyskinesias in the long term or to address the many non-motor symptoms that are typical of the advanced stages of the disease. The aim of this study was to obtain a European Consensus on the use of safinamide, considering the efficacy of this compound on motor symptoms and motor complications, its effect on non-motor symptoms (NMS), quality of life in patient with PD and how its clinical effect is perceived by clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Safinamide ( Figure 1(a )) is a reversible inhibitor of MAO-B that has both dopaminergic and glutamatergic functions [ 13 ]. Current evidence suggests that safinamide may be useful for the treatment of multiple neurological disorders including neuromuscular disorders, Parkinson’s disease (PD), stroke, and multiple sclerosis [ 14 , 15 ]. Evidence from multiple preclinical studies has shown that safinamide possesses antioxidant capacity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%